ACETYLATION AND CHARACTERIZATION OF THREE CULTIVARS OF UNRIPE PLANTAIN (Musa species) STARCH - , OGUNDIPE, Oladeinde Olatunde; OGUNBISI, Mercy Adenike; AKINSANYA, Nurudeen Akinwale; ADEMOLA, Oluwatoyin; ATERE, Bosede Adeola; AKINWANDE, Femi Fidelis (IJRDO-Journal of Applied Science, 2020)
Three cultivars of mature unripe plantain (giant horn, agbagba, French horn), consumed in Nigeria had their native starches extracted, and chemically modified by acetylation. Acetylated and native starches were evaluated for physicochemical and pasting and functional properties. Moisture content (MC), ash content (AC), amylose content (AMC) and blue value (BV) of native starches ranged between (10.6 and 12.8%), (0.02 and 0.04%), (17.23 and 22.38%), (0.21 and 0.29nm) respectively. For native plantain starches Functional property values obtained ranged as follows solubility (1.50 and 2.50%), swelling power (SP) (5.58 and 8.15g/g), bulk density (BD) (0.79 and 0.82g/ml), water absorption capacity (WAC) (60.45 and 68.50%). Acetylation treatment was observed to cause a significant difference (P<0.05) between the mean scores, for physicochemical and functional properties of plantain starches. Acetyl and degree of substitution of acetylated starches ranged between (2.05 and 7.20%), (0.08 and 0.28) respectively. Acetylated starches functional properties such as solubility, SP, BD and WAC of acetylated starches ranged between (2.50 and 4.50%), (8.23 and 9.29g/g), (0.73 and 0.78g/ml), (81.50 and 86.50%) respectively. Acetylation significantly (P<0.05) reduced the peak, trough, breakdown, final, setback viscosity and pasting temperature of the three cultivars of plantain starches in this study, but increased the peak time.